Characterization and mitigation of interference between GNSS radio occultation and reflectometry signals for low‐altitude occultations. Issue 3 (27th June 2020) - Collett, Ian; Morton, Y. T. Jade; Wang, Yang; Breitsch, Brian
Abstract: This research investigates the mutual interference between a GNSS signal refracted through the atmosphere and the same signal reflected from the surface below. For low‐altitude occultations, the reflected signal can be present as multipath when tracking the direct signal. This poses a problem when making remote sensing measurements using GNSS‐RO or GNSS‐R techniques. Here, this issue is addressed in the context of GNSS data collected by a mountaintop receiver on the Hawaiian island of Maui. First, an elevation‐angle threshold, below which the reflected signal can be present as multipath on the direct signal, is calculated for the mountaintop geometry. Next, the first steps are taken to mitigate the mutual interference between the direct and reflected signals. A frequency‐domain filtering approach and a time‐domain smoothing approach are applied to the signal intensity in an effort to separate the multipath contribution and the direct signal contribution.